Anatomical study of the eye arterial blood supply in adult river buffalo (Bubalus bubalis) - Beyrami, Amineh (Vet Res Forum, 2021)
Obtaining information about the eye arterial supply in the buffalo can be a criterion for ocular diseases diagnosis and give a morphological basis for even more researches on the related clinical surgery of this animal. The aim of the present study was to describe the course and branches of the arteries supplying the eye in the adult river buffalo (Bubalus bubalis). In this study, the heads of eight buffaloes were prepared from the public slaughterhouse and dissected to study the eye arterial supply. This research results showed that the eye blood supply in the buffalo originates from the external ophthalmic, internal ophthalmic, superficial temporal and malar arteries. The external ophthalmic artery was given rise to branches to take part in the ophthalmic rete mirabile formation and also given off lacrimal, external ethmoidal, supraorbital and ciliary arteries as well as muscular branches to supply the eye ball and extra-ocular muscles. The internal ophthalmic artery was one of the sources of lateral posterior long ciliary artery. The superficial temporal artery was detached off some branches to supply the lateral angle of inferior and superior eyelids as well as lacrimal branch to supply lacrimal gland. The malar artery was originated from the infra-orbital artery and its branches were supplied the medial angle of inferior, superior and third eyelids. There were no obvious differences between buffalo and yak regarding arteries supplying the eyes. However, there were minor differences between buffalo and oxen, sheep and goat and there were obvious differences between buffalo and camel and giraffe.